2016
DOI: 10.1111/ijcs.12302
|View full text |Cite
|
Sign up to set email alerts
|

The influence of source attractiveness on self‐perception and advertising effectiveness for 6‐ to 7yearold children

Abstract: Van de Sompel, D. and Vermeir, I. (2016). The influence of source attractiveness on self-perception and advertising effectiveness for 6-to 7-year-old children. AbstractThe objective of this article is to examine the effects of using attractive peer models in advertising for 6-7 year old children. This age is important in children's development, as children of that age are not yet fully aware of the persuasive intent of advertising, are more focused on perceptual than on cognitive information in ads and are mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 54 publications
(98 reference statements)
0
10
0
2
Order By: Relevance
“…Furthermore, the physical appearance or attractiveness of the source plays a major role in the endorsers’ credibility and, consequently, persuasiveness (Kahle and Homer, 1985; Kamins, 1989; McCracken, 1989; Ohanian, 1991). Even among children, using attractive peer models has been shown to increase advertising effectiveness (e.g., Van de Sompel and Vermeir, 2016). Source attractiveness is driven by factors such as perceived similarity, familiarity, and likeability of the source.…”
Section: Social Media Influencers As a New Source In Advertising Targmentioning
confidence: 99%
“…Furthermore, the physical appearance or attractiveness of the source plays a major role in the endorsers’ credibility and, consequently, persuasiveness (Kahle and Homer, 1985; Kamins, 1989; McCracken, 1989; Ohanian, 1991). Even among children, using attractive peer models has been shown to increase advertising effectiveness (e.g., Van de Sompel and Vermeir, 2016). Source attractiveness is driven by factors such as perceived similarity, familiarity, and likeability of the source.…”
Section: Social Media Influencers As a New Source In Advertising Targmentioning
confidence: 99%
“…People see hundreds of persuasive marketing messages every day—everything from traditional television advertisements to sponsored social media posts (Committee on Communications, ; Hill Holliday, ; Raab, ). This persistent exposure to persuasive messages has been linked to a variety of negative effects, including an increase in the consumption of unhealthy foods (e.g., Gilbert‐Diamond et al, ), a decrease in perceived self‐worth (e.g., Van de Sompel & Vermier, ), and an increase in materialistic tendencies (Watkins, Aitken, Robertson, Thyne, & Williams, ). However, frequent exposure to commercial persuasion can also lead to more adaptive outcomes, including greater knowledge and understanding about how marketing tactics work and thus a more sophisticated ability to cope with persuasion attempts (e.g., Boush, Friestad, & Rose, ).…”
Section: Introductionmentioning
confidence: 99%
“…This observed reality has a specific reading according to the previous literature that has been exposed in the theoretical framework. We refer to the fact that children begin to develop an awareness of their body image (and a potentially negative selfassessment) from the age of eight (Van de Sompel, 2017). For this reason, establishments that target a more childish audience, under the age of eight, do not have to resort to "adulterated" beauty standards to draw attention to them and to take them as referents, since studies have demonstrated that, for this According to the age represented Non according to the age represented type of public, the corporal references are still secondary and practically non-existent.…”
Section: Discussionmentioning
confidence: 99%